Bismuth oxysulfide modified ZnO nanorod arrays as an efficient electron transport layer for inverted polymer solar cells. Issue 24 (5th June 2019) - Wu, Zuping; Yu, Huangzhong; Shi, Shengwei; Li, Yanping
Abstract : Vertically aligned zinc oxide nanorod arrays (ZnO NRAs) are expected to provide a direct and stable electron transport pathway in polymer solar cells (PSCs) so as to enhance charge carrier collection and transport. Abstract : Vertically aligned zinc oxide nanorod arrays (ZnO NRAs) are expected to provide a direct and stable electron transport pathway in polymer solar cells (PSCs) so as to enhance charge carrier collection and transport. However, the electrical coupling of ZnO NRAs/active layer and the surface defects limit the improvement of device performance. The modification of the surface of ZnO NRAs is an effective way to solve this problem. In this paper, we report the enhanced performance of inverted polymer solar cells (IPSCs) composed of poly(3-hexylthiophene) (P3HT):[6, 6]-phenyl C61 -butyric acid methyl ester (PCBM) blends by using bismuth oxysulfide (Bi2 O2 S) nanoparticle modified ZnO NRAs as an efficient electron transport layer (ETL). It is found that the modification of the ZnO NRA surface with Bi2 O2 S nanoparticles can effectively passivate the surface traps, reduce the series resistance, improve the electrical coupling of ZnO NRAs/active layer, and enhance the crystallinity of the active layer. Consequently, the open-circuit voltage ( V oc ), the short-circuit current ( J sc ) and the fill factor (FF) of the PSCs are considerably improved. The resulting power conversion efficiency (PCE) is improved to 3.61% as compared to 2.47% for the reference device without Bi2 O2 S modification. Moreover, this approach can also successfully improve the performance of other IPSCs composed of poly[(2, 6-(4, 8-bis(5-(2-ethylhexyl)thiophen-2-yl)-benzo[1, 2- b :4, 5- b ′]dithiophene))- alt -(5, 5-(1′, 3′-di-2-thienyl-5′, 7′-bis(2-ethylhexyl)benzo[1′, 2′- c :4′, 5′- c ′]dithiophene-4, 8-dione))] (PBDB-T):3, 9-bis(2-methylene-(3-(1, 1-dicyanomethylene)-indanone))-5, 5, 11, 11-tetrakis(4-hexylphenyl)-dithieno[2, 3- d :2′, 3′- d ′]- s -indaceno[1, 2- b :5, 6- b ′]dithiophene (ITIC) blends. The PCE of the device based on the Bi2 O2 S-modified ZnO NRAs is improved to 9.89% from 7.76% for the reference device without Bi2 O2 S nanoparticle modification. This work not only provides an effective means of surface modification of ZnO NRAs, but also demonstrates that the Bi2 O2 S material has potential for application in photovoltaic devices.